The SmartAG Partner: CCAFS East Africa Quarterly Newsletter, October – December 2015 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
We are pleased to share with you the first issue (in 2016) of the SmartAG Partner - a quarterly newsletter of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) East Africa (EA). We share the key highlights from CCAFS EA research and policy engagement initiatives from the last quarter of 2015.